Strategi Penanganan Non-Perfoming Loan dan Implikasinya terhadap Stabilitas Keuangan Bank: Studi Kasus pada Bank Sulselbar - Nurul Chalisa Majiding; Ambarwati Akib; Dwi Utami; Sri Utami; Magfirah Wahyu Ramadhani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study examines the strategies employed by Bank Sulselbar to manage non-performing loans (NPL) and their implications for the bank’s financial stability. Using a qualitative case study approach, in-depth interviews and conducted alongside internal document analysis. Findings reveal that a combination of preventive measures—such as strict credit appraisal and ongoing monitoring—and curative actions—including loan restructuring, intensive debtor communication, and collateral execution—have effectively contained NPLs below the central bank’s threshold of 5%. Despite external shocks from the COVID-19 pandemic and regional natural disasters, Bank Sulselbar maintained a Loan-to-Deposit Ratio (LDR) of 88% and Capital Adequacy Ratio (CAR) above regulatory minima. However, rising NPLs in the agricultural and MSME segments necessitate portfolio diversification and enhanced stress testing to safeguard long-term liquidity and solvency. This research contributes to localized risk management literature and offers practical insights for regulators and regional banks.